Tribological Properties of SPS Reactive Sintered Al/MoS2 Composites - Marek Kostecki; Krzysztof Kulikowski; Dorota Moszczyńska; Andrzej Roman Olszyna (Metals)
In search of opportunities to improve mechanical properties and abrasion resistance, composites based on aluminum reinforced with MoS2 particles were produced. The authors’ previous research indicated the possibility of obtaining hard dispersion precipitates of the Al12Mo intermetallic phase as a result of the reaction of the composite components at a temperature exceeding 550 °C during the SPS (Spark Plasma Sintering) process. This work focused on optimizing the SPS consolidation process and assessing the microstructure and mechanical properties of the obtained materials. A series of experiments proved that by increasing the amount of the strengthening phase and increasing the process temperature, a significant amount of Al12Mo and Al5Mo strengthening phases is produced. Exceptionally good dispersion of reinforcing particles and the presence of layered MoS2 crystals, while ensuring optimal parameters of the synthesis process, lead to a change in friction mechanisms and improved abrasion resistance through an approximately 30-fold decrease in the wear factor.